PRAYING OF THE BUDDHIST MANTRA "RATTANA SUTRA" TO HEAL THAI PEOPLE’S MINDS AMID THE EPIDEMIC SITUATION OF THE CORONAVIRUS DISEASE 2019 (COVID-19) - Chimpleewat, Kritsada (Journal of Buddhist Anthropology, 2022)
The objective of this article presents the results of a study on Praying of the Buddhist mantra "Rattana Sutra" concept, following special resolution 4/2564 dated May 5, 2021, B.E. of the National Office of Buddhism to heal the mental state of the people in society amid the epidemic situation of the Coronavirus Disease 2019 (COVID-19). This situation affects the economy, society, and education, and public health and people’s mind. Because on the other hand, it has created great panic and anxiety for the people. There is also a lot of negative news was presented continuously through social media. Including the announcement of various government policies or measures that still affect people’s livelihoods and careers and influence the mental state of people greatly. The results showed that the purpose of reciting the Sutra is to eliminate all three dangers as they appear in the Sutra, namely a famine, ghost and disease. This is consistent with the concept of the Office of Buddhism by the Sangha who wants to heal people’s minds affected by this epidemic situation. It is an operation based on the principle of the mind as the master while the body is the slave. ฺBecause they believe that mental health is good physical health will be good as well. And such activities it started on May 11, 2021, the first day at Wat Pho and then proceed to all temples across the country.